2017
DOI: 10.3389/fpls.2016.02048
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Phloem Unloading and Expression of Sucrose Transporters in Vegetative Sinks of the Parasitic Plant Phelipanche ramosa L. (Pomel)

Abstract: The plant-parasitic plant interaction is a interesting model to study sink-source relationship and phloem unloading. The parasitic plants, such as the achlorophyllous plant Phelipanche ramosa, connect to the host phloem through the haustorium and act as supernumerary sinks for the host-derived photoassimilates, primarily sucrose. The application of the fluorescent symplastic tracer, carboxyfluorescein (CF) derived from carboxyfluorescein diacetate (CFDA), to the leaves of the host plant (Brassica napus) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…To determine the predicted subcellular localization of soybean NRAMP proteins, six GmNRAMP proteins were selected to generate subcellular localization constructs, then transient expression in Arabidopsis protoplasts, which were widely used in subcellular localization analysis of genes not only for soybean, but also for other plant species (Zhang et al, 2016 ; Chong et al, 2017 ; Chu et al, 2017 ; Péron et al, 2017 ; Xu et al, 2017 ). Specifically, the coding region of each GmNRAMP gene was amplified with gene-specific primers shown in Table S3 .…”
Section: Methodsmentioning
confidence: 99%
“…To determine the predicted subcellular localization of soybean NRAMP proteins, six GmNRAMP proteins were selected to generate subcellular localization constructs, then transient expression in Arabidopsis protoplasts, which were widely used in subcellular localization analysis of genes not only for soybean, but also for other plant species (Zhang et al, 2016 ; Chong et al, 2017 ; Chu et al, 2017 ; Péron et al, 2017 ; Xu et al, 2017 ). Specifically, the coding region of each GmNRAMP gene was amplified with gene-specific primers shown in Table S3 .…”
Section: Methodsmentioning
confidence: 99%
“…Through the haustorium, the parasite diverts water, and nutrients from the host (Westwood, 2013), leading to severe yield loss, and quality in numerous vegetables crops (Joel et al, 2007; Pérez-de Luquea et al, 2010; Fernández-Aparicio et al, 2016). It was suggested that once the connection between the parasite and the host roots is established, the parasite functions as an active sink, redirecting solutes away from autotrophic sink tissues and subsequently leading to a decrease in the accumulation of host biomass (Péron et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The movement of GFP that is expressed in the host’s CCs to parasitic plants has been reported in a stem parasitic plant ( Cuscuta reflexa ) [ 7 , 8 ] and root parasitic plants ( P. ramosa and P. aegyptiaca ) [ 9 , 10 ]. GFP is smaller (27 kDa) than the typical size exclusion limit (SEL) of plasmodesmata between CCs and SEs (that can be as large as 67 kDa) [ 13 ], so GFP synthesized in CCs can be translocated to SEs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, transport function of haustorial phloem has been demonstrated by using symplasmic tracers. Studies using fluorescent symplasmic tracers have demonstrated that carboxyfluorescein or CC-expressed green fluorescent protein (GFP) can be transported from host to parasite through haustoria in Cuscuta reflexa [ 7 , 8 ], Phelipanche ramosa [ 9 ], and P. aegyptiaca [ 10 ]. In haustoria of a facultative parasitic plant, Phtheirospermum japonicum , carboxyfluorescein was transported from the host’s sieve tubes to haustoria, but CC-expressed GFP was not, implying the lack of phloem-to-phloem connection between the host and parasite, or difficulty in GFP movement due to its size [ 11 ].…”
Section: Introductionmentioning
confidence: 99%